META-THEORY’S PERSPECTIVE OF FUNCTIONALIST VIEW ON DEVIANCE IN SCHOOLS: PROSPECTS FOR THE FUTURE OF NIGERIAN SCHOOLS - Inuwa, Awwalu Muhammad (Sokoto Educational Review, 2020)
This paper is on Meta theory’s perspective of functionalist view oh deviance in schools: Prospect for the future of Nigerian schools. Sociologists of education explore almost all social problems in schools, of which many are manifestation of societal behaviours, among which are deviant act (anti-social behaviour). The paper uses Meta theoretical perception to study the functionalist idea of deviance in Nigerian schools. Single sociological theory has fail to yield good result; therefore meta theory stands a better chance as it is the amalgam of two or more theories in the study of one social problem. The paper adopted Meta theory on the functionalist view of deviance as it relates to Nigerian schools. The Meta theoretical perception of functionalist view on deviance in schools is highlighted. Among which deviance function to promote the unification of values by revisiting the strength of social rules and its dysfunction causes treat to school authority, and the prospect is that deviance are view from multiple dimensions, therefore, resolved to adopt various strategies to curtail deviance problems. Among the recommendation emanating from Meta theory are; the social gap and social stratification that exist in society should by no means influence school activities as this frustrate some students to stray, and teachers should desist from labeling students with negative names, because such attitude helps in promoting deviant acts and negative self-fulfillment prophecy among students.